ASEAN Migrants: A Boon for Taiwan’s Aging Populace - Hong-Ming Huang; Jenn-Jaw Soong (JAS (Journal of ASEAN Studies), 2013)
Taiwan is home to a rapidly growing aging population as life expectancy rates increase and birth rates go down in this island. The government of Taiwan opted to bring in migrant workers to care for the elderly following a shortage in adequate domestic manpower who were willing to take on the positions of caregivers for the elderly. In time, eldercare in Taiwan switched hands: from the actual families of the elderly to migrant workers coming in from across the Southeast Asian region. Questions have arisen in light of this development. Is the government policy that allows for Southeast Asian migrants to care for the elderly in Taiwan a good one, or a bad one? Who benefits most from this deal: the elderly, their families or the migrant care workers? Is providing care for the elderly in their own homes by just one caregiver the only option? And can such a policy help both ends: the elderly person who requires safer care, and the migrant care worker whose labor rights require full protection? This paper, drafted out following the review of relevant literature and the conducting of interviews by Hong-Ming Huang and Jenn-Jaw Soon, analyzes the political-economic aspects of this policy and offers certain recommendations and conclusions. One conclusion is the fact that Southeast Asian workers take better care of the elderly in Taiwan when eldercare is provided through institutions, rather than if the care was provided by just one foreign caregiver engaged directly by families of the elderly. The positive effects of ‘institution-style’ workers are reflected in the work performance, life quality and management as well as labor rights protection.